The application of plant growth-promoting rhizobacteria in Solanum lycopersicum production in the agricultural system: a review - Adedayo,Afeez Adesina; Babalola,Olubukola Oluranti; Prigent-Combaret,Claire; Cruz,Cristina; Stefan,Marius; Kutu,Funso; Glick,Bernard R. (PeerJ, 2022)
Food safety is a significant challenge worldwide, from plantation to cultivation, especially for perishable products such as tomatoes. New eco-friendly strategies are needed, and beneficial microorganisms might be a sustainable solution. This study demonstrates bacteria activity in the tomato plant rhizosphere. Further, it investigates the rhizobacteria’s structure, function, and diversity in soil. Rhizobacteria that promote the growth and development of tomato plants are referred to as plant growth-promoting bacteria (PGPR). They form a series of associations with plants and other organisms in the soil through a mutualistic relationship where both parties benefit from living together. It implies the antagonistic activities of the rhizobacteria to deter pathogens from invading tomato plants through their roots. Some PGPR are regarded as biological control agents that hinder the development of spoilage organisms and can act as an alternative for agricultural chemicals that may be detrimental to the health of humans, animals, and some of the beneficial microbes in the rhizosphere soil. These bacteria also help tomato plants acquire essential nutrients like potassium (K), magnesium (Mg), phosphorus (P), and nitrogen (N). Some rhizobacteria may offer a solution to low tomato production and help tackle food insecurity and farming problems. In this review, an overview of soil-inhabiting rhizobacteria focused on improving the sustainable production of Solanum lycopersicum.
Keywords: Biocontrol; Biofertilizer; Environmental health; Food safety; Plant health; Tomato